Resiliencia de los Sistemas Eléctricos - Paredes Tapia, Luis Ángel (2020)
Electrical systems currently face a new technical andoperational paradigm, subject to the development,positioning, and maturity of different renewable energysources under conditions of access to energy and theirefficient consumption. Electrical systems are the largestengineering structures in energy systems. Therefore, theyare affected and vulnerable to being affected by differentcontingencies and disturbances that can cause the powersupply to be suspended. The studies and managementassociated with the safety and reliability actions ofthe electrical systems have been carried out under thesupposed considerations of outputs and/or unavailabilityof the elements that make up the network. The analysisand evaluation of the events of a low probability ofoccurrence but that cause high impacts in the systemsare studied in this document. Through a methodologicalanalysis the resistance of the electrical systems, theirlimitations, characterization, and differences with thereliability are exposed. As well as the metrics and researchneed related to resilience in the different functional stagesof electrical systems.